Effects of extruded-expelled soybean meal and solvent extracted soybean meal level of growth performance of weanling pigs - Lawrence, K.R.; Hastad, C.W.; Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 350 weanling pigs (initially 15.7 lb) were used to evaluate the effects of soybean meal source and level on growth performance of early weaned pigs. Dietary treatments included a control diet containing no soybean meal, or diets containing 20% or 40% of either solvent extracted soybean meal (SBM) or extruded-expelled soybean meal (EESOY). The SBM and EESOY were analyzed for trypsin inhibitor (0.7 mg TI/g and 1.8 mg TI/g, respectively) to ensure quality, and actual crude protein values (46.9% and 48.3% as-fed, respectively) were used in diet formulation. From d 0 to 14, increasing EESOY decreased ADG and ADFI (linear, P<0.01), but improved F/G (linear, P<0.05). Increasing SBM decreased ADFI (linear, P<0.02), but improved F/G (linear, P<0.01). No differences (P>0.05) were found between soybean meal sources throughout the trial. The results of this study suggest extrudedexpelled soybean meal processed properly and fed in diets immediately after weaning did not improve growth performance of nursery pigs relative to conventional solvent extracted soybean meal. When EESOY or SBM was included at 40% in diets fed immediately after weaning, growth performance of weanling pigs was poorer than if fed at lower levels (20%). Feeding properly processed EESOY resulted in similar growth performance compared to feeding SBM.
Keywords: Weanling pigs; Soybean meal; Performance; Swine